Pengaruh Harga, Promosi dan Store Atmosphere terhadap Keputusan Pembelian Konsumen Omah Langit Semarang - Chicilia Ayu Zherlina; Mulyo Budi Setiawan (Universitas Batanghari Jambi, 2023)
This study analyzes the effect of price, promotion and store atmosphere on consumer purchasing decisions of Omah Langit Semarang. The population used in this study were all customers who had visited and bought at Omah Langit Semarang. The sampling technique in this study used a purposive sampling technique with a total sample of 100 respondents. The data collection method used is the questionnaire method, the data that has been collected is then analyzed using instrument testing, model testing, and hypothesis testing. There are three hypotheses tested in this study, the results of the study indicate that price, promotion and store atmosphere have a positive and significant effect on purchasing decisions.